2019
DOI: 10.2147/ijn.s200847
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hybrid curcumin–phospholipid complex-near-infrared dye oral drug delivery system to inhibit lung metastasis of breast cancer</p>

Abstract: Background: Oral route of administration is preferred for treating breast cancer, especially when continued disease management with good tolerability is required; however, orally administered chemotherapeutics combined with near-infrared (NIR) dyes are hindered by the low bioavailability, insufficient for the desired therapeutic efficacy. In this study, we developed a hybrid self-microemulsifying drug delivery system for co-loading curcumin–phospholipid complex and NIR dye IR780 (CUR/IR780@SMEDDS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…This deviation of the IR/SBMA-BSA NPs and IR+DOX/SBMA-BSA NPs absorptions toward the NIR zone has been attributed to changes in solvents' polarity and/or to different hydrophobic interactions occurring in the nanoparticles' core. [7,14,15,36] Considering that 808 nm light will be used in the photothermal experiments, the higher absorption of the nanoformulations at this wavelength may lead to a greater therapeutic outcome.…”
Section: Nir Absorption and Photothermal Capacity Of Ir/sbma-bsa Nps mentioning
confidence: 99%
See 1 more Smart Citation
“…This deviation of the IR/SBMA-BSA NPs and IR+DOX/SBMA-BSA NPs absorptions toward the NIR zone has been attributed to changes in solvents' polarity and/or to different hydrophobic interactions occurring in the nanoparticles' core. [7,14,15,36] Considering that 808 nm light will be used in the photothermal experiments, the higher absorption of the nanoformulations at this wavelength may lead to a greater therapeutic outcome.…”
Section: Nir Absorption and Photothermal Capacity Of Ir/sbma-bsa Nps mentioning
confidence: 99%
“…[10,11,12] To address this limitation, chemotherapeutic agents have been loaded into NIR-responsive nanomaterials. [11,[13][14][15] The temperature increase achieved upon NIR laser irradiation can trigger the release of the chemotherapeutic agents from the nanomaterials into the tumor zone, further contributing to an on-demand treatment. [8,16,17] In this way, the chemo-PTT mediated by nanomaterials can lead to an enhanced therapeutic effect when compared to the single therapies (nanomaterials' mediated PTT or chemotherapy).…”
Section: Introductionmentioning
confidence: 99%
“…However, its clinical application has been limited because of its low solubility and rapid metabolism in vivo. [2][3][4][5][6][7][8][9] In the past decades, nanocarriers have been rapidly developed for drug delivery to increase solubility, prolong duration in vivo, improve tumor-selective cytotoxicity, and reduce drug exposure to normal tissues including polymeric nanoparticles, inorganic nanoparticles, and liposomes. [10][11][12][13][14][15][16][17][18] Polymeric nanocarriers may be composed of a synthetic polymer or natural polymer, both of which have exhibited good biocompatibility, an easily manipulated chemical structure, and stimuli-responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Xu et al [ 38 ] reported improved inhibitory effects of polyphenols on 4T1 cancer cells. Studies by Liu et al [ 39 , 40 , 41 ] have reported improved bioavailability of bioactive compounds, thus improving their potential inhibiting effect on breast cancer cells. The present study findings agree with the abovementioned reported studies, and those of other researchers such as Moeini [ 21 ] where phytosomes and other lipid phospholipid nanocarriers improved bioavailability of bioactive compounds, thus improving their efficacy in inhibiting breast cancer cells growth.…”
Section: Resultsmentioning
confidence: 99%